Investigation of in-situ alloying of maraging Steel M789 via direct energy deposition - M Mohamed Azfar (Nanyang Technological University, 2023)
M789 maraging steel is a low-alloy, high-strength steel widely used in corrosive environments. This study investigated the in-situ alloying of Maraging steel M789 via Direct Energy Deposition (DED). The DED method is a form of additive manufacturing (AM) that employs laser or electron beams to dissolve and fuse metal particles onto a substrate. In this study, maraging steel M789 was alloyed with varying amounts of 316L alloy to produce TRIP-maraging steel. The DED fabricated samples were then characterized using microstructural analysis techniques, such as Scanning Electron Microscopy (SEM) equipped with an electron backscatter diffraction detector (EBSD). Further characterization, such as tensile tests and X-ray diffraction (XRD) analyses were conducted. The findings demonstrated that the addition of 316L to M789 maraging steel enhanced the alloy's strength, while maintaining high strength. However, in-situ alloying resulted in microstructural changes, such as the formation of austenite. Overall, this investigation demonstrates the viability of in-situ alloying of maraging steel M789 via DED to produce alloys with enhanced properties for specific marine and offshore too.